Remittances Channel and Fiscal Impact in the Middle East, North Africa, and Central Asia - Abdih, Yasser (IMF Working Papers; Working Paper, 2012)
This paper identifies a remittances channel that transmits exogenous shocks, such as business cycles in remittance-sending countries, to the public finances of remittance-receiving countries. Using panel data for remittance-receiving countries in the Middle East, North Africa, and Central Asia, three types of results emerge. First, remittances appear to be strongly procyclical vis-a-vis sending country income. Second, remittances tend to be spent on consumption of both imported and domestically produced goods, rather than on investment. Third, shocks in the sending countries are transmitted via remittances to the public finances - specifically, tax revenues - of receiving countries. In the case of the 2009 global downturn, this impact was particularly strong for several countries in the Caucasus and Central Asia, whereas in the subsequent recovery in 2010 virtually all receiving countries benefitted from an upturn in remittance-driven tax revenues.